I assume we are solving?
multiply each term by x^4
9 - 35x^2 - 4x^4 = 0
4x^4 + 35x^2 - 9 = 0
(x^2 +9)(4x^2 - 1) = 0
x^2 = -9 or x^2 = 1/4
x = ± 3i or x = ± 1/2
let z = x^-2
then z^2 = x^-4
9 z^2 - 35 z - 4 = 0
(9z+1)(z-4) = 0
z = 4 or z = -1/9
you take it from there
Answer this Question
algebra - factor the expression 4xsquared+35x+24 my answer: (4x+3)(x-8) 4x2 +35x...
college algebra - 9x^-4-35x^-2=0
college algebra - GCF -x^7,-7x^3,-35x^6
Algebra - Rewrite the middle term as the sum of two terms and then factor ...
Math - f(x) = 5x^2 - 35x I converted ^ that equation to.. 5x^2-35x = 0 How do I ...
7th grade math - what is the equivalent expressin of 7(5x) 35x ? 35x
Math - Could someone please explain this problem to me. I need to factor and ...
Algebra - Andrew factored the expression 28x^3-42x^2+35x as 7x(4x^2+6x-5). But ...
PRE-ALGEBRA PT.2 - 12 + 0.35x = 20.05 A. 91.5 B. 57.3 C. 2.8175 D. 23 I GOT D
algebra - factor completely 75x^4+35x^3-10x^2